Tea and lycopene protect against prostate cancer - Jian, Le; Lee, Andy; Binns, Colin (H E C Press, 2007)
Prostate cancer is the most common male cancer in developed countries and is increasing in the developing world. Its long latency and geographical variation suggest the possibility of prevention or postponement of onset by dietary modification. To investigate the possible joint effect of lycopene and green tea on prostate cancer risk, a case-control study was conducted in Hangzhou, China, with 130 prostate cancer patients and 274 hospital controls. Information on tea and dietary intakes, and possible confounders was collected using a structured questionnaire. The risk of prostate cancer for the intake of tea and lycopene and their joint effect were assessed using multivariate logistic regression models. Prostate cancer risk was reduced with increased consumption of green tea. The protective effect of green tea was significant (odds ratio 0.14, 95% CI: 0.06-0.35) for the highest quartile relative to the lowest after adjusting for total vegetables and fruits intakes and other potential confounding factors. Intakes of vegetables and fruits rich in lycopene were also inversely associated with prostate cancer risk (odds ratio 0.18, 95% CI 0.08-0.39). Interaction analysis showed that the protective effect from tea and lycopene consumption was synergistic (p<0.01). This study suggests that habitual drinking tea and intakes of vegetables and fruits rich in lycopene could lead to a reduced risk of prostate cancer in Chinese men.Together they have a stronger preventive effect than either component taken separately. This is the first epidemiological study to investigate the joint effect between tea drinking and lycopene intake.